(untitled) (Research, Society and Development, 2022)
Introduction: The International Classification of Functioning, Disability and Health describes health and the states related to it, from the perspective of a biopsychosocial model. In Brazil, the use of the tool by occupational therapists is regulated by the class council, favoring its wide use in therapeutic planning. Objective: To identify, through the literature, how the Classification is used by occupational therapists. Method: This is an integrative literature review. The literature search was carried out in the Scientific Electronic Library Online (SciELO), in the Virtual Health Library (BVS) and in PubMed, having as selection criteria articles published between 2010 and 2020, in Portuguese, English or Spanish, and that were fits the theme of the use of Classification by Occupational Therapy. Result: 67 articles were selected and they were categorized into five groups according to the form of use. Of the components of the tool, the study identified that 91% of the articles used the Activity and Participation component, 73% used the Body Functions, 52% used the Environmental Factors, 46% used the Body Structures and twelve 18% used the Personal Factors. Conclusion: Occupational therapists have used the Classification in their professional practice within the various possibilities presented by the World Health Organization, demonstrating that the tool can be used as an auxiliary for the profession.